2003
DOI: 10.1097/00126334-200307010-00004
|View full text |Cite
|
Sign up to set email alerts
|

HIV Insertions Within and Proximal to Host Cell Genes Are a Common Finding in Tissues Containing High Levels of HIV DNA and Macrophage-Associated p24 Antigen Expression

Abstract: HIV integration within host cell genomic DNA is a requisite step of the viral infection cycle. Yet, characteristics of the sites of provirus integration within the host genome remain obscure. The authors present evidence that in diseased tissues showing a high level of HIV DNA and macrophage-associated HIV p24 antigen expression from end stage forms of HIV disease, HIV-1 integration sites were favored within genes and transcriptionally active host cell genomic loci. Using an inverse PCR (IPCR) technique that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 18 publications
3
48
0
Order By: Relevance
“…In these earlier studies, we identified an abundance of HIV recombinants (80), which could arise due to superinfection of long-lived HIV-infected macrophages. Furthermore, Mack et al (96) found that a large variety of diseased tissues derived from cART-negative autopsy tissues from patients who died with AIDS lymphoma or AIDS dementia contained amplifiable amounts of HIV DNA. In these tissues, p24 antigen staining was localized predominantly to macrophages in-terspersed in a background of p24-negative lymphocytes; this type of staining was not seen in nondiseased tissues (96).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these earlier studies, we identified an abundance of HIV recombinants (80), which could arise due to superinfection of long-lived HIV-infected macrophages. Furthermore, Mack et al (96) found that a large variety of diseased tissues derived from cART-negative autopsy tissues from patients who died with AIDS lymphoma or AIDS dementia contained amplifiable amounts of HIV DNA. In these tissues, p24 antigen staining was localized predominantly to macrophages in-terspersed in a background of p24-negative lymphocytes; this type of staining was not seen in nondiseased tissues (96).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Mack et al (96) found that a large variety of diseased tissues derived from cART-negative autopsy tissues from patients who died with AIDS lymphoma or AIDS dementia contained amplifiable amounts of HIV DNA. In these tissues, p24 antigen staining was localized predominantly to macrophages in-terspersed in a background of p24-negative lymphocytes; this type of staining was not seen in nondiseased tissues (96). These macrophage p24-rich tissues contained HIV integrated within genetic activation loci.…”
Section: Discussionmentioning
confidence: 99%
“…However, non-AIDS-defining malignancies have been on the increase since the availability of combination antiretroviral therapy, and the underlying cause of these additional malignancies is poorly understood (25)(26)(27). Although the activation of protooncogenes due to normal HIV-1 integration seems to be extremely rare, which is one of the reasons lentiviral vectors are being tested for gene therapy, there is a report suggesting that HIV integration can cause oncogene activation (28). The fact that the treatment with INSTIs leads to aberrant insertions that are accompanied by rearrangements of the host genome could increase the potential for the insertional activation of oncogenes and/or the inactivation of genes encoding tumor suppressors.…”
Section: Discussionmentioning
confidence: 99%
“…Control sequences were obtained from both a lymphocyte-depleted iliac lymph node and seminal vesicles. DNA was prepared, and the HIV copy number/genomic equivalent within specimens was quantitated as previously described (19). Immunohistochemistry on tissues to evaluate the sites of HIV expression was also performed as previously described (19).…”
Section: Methodsmentioning
confidence: 99%